Pembuatan Website Online Store Dilengkapi dengan Chatbot - Dinata, Fredickson; Mawardi, Viny Christanti; Hendryli, Janson (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
The advance of technology and the increased number of internet usage, have caused many companies to build their slot web as a way to market their product. But getting the attention of people isn’t an easy thing to achieve, so livechat and chatbot are implemented into the system to increase the quality of services. This chatbot was developed using the Vector Space Model which will calculate the similarity of each question and the input, before using the vector space model each question will be weighted with term weighting. The chatbot was tested directly and the result is calculated to get the precision of 0.813, recall of 0.751, and f-measurement of 0.766. From the results, we can say the performance of the chatbot is quite decent for it has increased the quality of the services which the online slot web provided.